Relationship between corporate governance and corporate financial distress : An empirical study of distressed companies in Turkey - Çatak, Çiydem (My University, 2012)
KURUMSAL YÖNETİM VE FİNANSAL SIKINTI ARASINDAKİ İLİŞKİ: TÜRKİYE ÖRNEĞİ Yaşanan büyük finansal ve kurumsal krizlerden sonra Kurumsal Yönetimin önemi huzla artmıştır.Ülkeler, şirketler ve diğer tüm kuruluşlar kendi yapılarına uygun olan kurumsal yönetim sistemini aramaya başlamışlardır. Ülkelerin düzenleyici ve denetleyici kuruluşları yol gösterici kurumsal yönetim kuralları yayınlamaya başlamış ve böylelikle şirketler ve kuruluşlara daha şeffaf, adil ve verimli olabilmeleri için yardımcı olmuşlardır. Kurumsal yönetimin önemini ortaya çıkaran bir çok ampirik çalışma yapılmıştır ve bu çalışmaların sayısı her geçen gün artmaktadır. Bu tezin amacı kurumsal yönetimle finansal sıkıntı arasında bir ilişki olup olmadığını belirlemektir. Bu amaçla 30 finansal sıkıntı çeken firma ve 30 sağlıklı firma seçilmiş ve bu firmaların kurumsal yönetim yapıları ikili lojistik regresyon analizi ile karşılaştırılmıştır.

RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND CORPORATE FINANCIAL DISTRESS: AN EMPIRICAL STUDY OF DISTRESSED COMPANIES IN TURKEY The importance of corporate governance has increased after the big corporate and financial crisis. Countries, companies and almost all organizations tried to find out the most suitable governance system for their own structures. To be a guide; the regulatory and supervisory authority of countries began to publish corporate governance principles to help the companies and other organizations to have a more transparent, fair and effective corporate governance structure. There are a lot of empirical studies that reveals the importance of corporate governance and the number of these studies is increasing every day. The purpose of this thesis is to determine whether there is a relationship between corporate governance and financial distress. In order to understand it; 30 financial distressed and 30 healthy firms are selected and the corporate governance structures of these companies are compared with Binary Logistic Regression Analysis.
Keywords: Finans; Kurumsal Yönetim; Muhasebe